(untitled) (Journal of Mathematical Study, 2021)
For a Banach space E, we give sufficient conditions for the Grothendieck property of ⨶_n,s,πE, the symmetric projective tensor product of E. Moreover, if E^∗ has the bounded compact approximation property, then these sufficient conditions are also necessary.